2021
DOI: 10.1038/s41467-021-21468-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to a hypomagnetic field attenuates adult hippocampal neurogenesis and cognition

Abstract: Adult hippocampal neurogenesis contributes to learning and memory, and is sensitive to a variety of environmental stimuli. Exposure to a hypomagnetic field (HMF) influences the cognitive processes of various animals, from insects to human beings. However, whether HMF exposure affect adult hippocampal neurogenesis and hippocampus-dependent cognitions is still an enigma. Here, we showed that male C57BL/6 J mice exposed to HMF by means of near elimination of the geomagnetic field (GMF) exhibit significant impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
82
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 63 publications
21
82
6
1
Order By: Relevance
“…On the other hand, HMF‐treated neuroblastoma cells are rounder and exhibit a reduction in cell process numbers and the amount of F‐actins, resulting in reduced cellular adhesion capacity and motility [Mo et al, 2016]. However, a recent study found that HMF exposure decreases NSC proliferation in the dentate gyrus of adult mice, which contradicts the aforementioned proliferative effects [Zhang et al, 2021]. A possible explanation could be differences in the age of the experimental animals or the different intensities of the HMF.…”
Section: The Biological Effects Of Hmfmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, HMF‐treated neuroblastoma cells are rounder and exhibit a reduction in cell process numbers and the amount of F‐actins, resulting in reduced cellular adhesion capacity and motility [Mo et al, 2016]. However, a recent study found that HMF exposure decreases NSC proliferation in the dentate gyrus of adult mice, which contradicts the aforementioned proliferative effects [Zhang et al, 2021]. A possible explanation could be differences in the age of the experimental animals or the different intensities of the HMF.…”
Section: The Biological Effects Of Hmfmentioning
confidence: 99%
“…Mitochondria play a predominant role in generating ROS and aerobic metabolism, which are also affected by HMF. On the one hand, HMF decreases ROS levels in many cancer cell lines and neurocytes, accompanied by suppressive or proliferative effects on cell growth and survival [Martino et al, 2010; Zhang et al, 2021], but increases cellular ROS levels in mouse skeletal muscle cells. Notably, cosmic radiation causes the accumulation of ROS, and the combined effects of HMF and radiation on ROS is an issue to be further studied.…”
Section: Mechanisms Of Hmf Biological Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…后几乎检测不到 [25] , 但同时也有研究结果表明在衰老过程中可以检测到海马神经发生水平的下 降 [22] 。关于人类海马是否存在神经发生还没有定论,还需要进一步证实。而在啮齿动物中普遍 存在成体海马神经发生,一方面,成体海马神经发生与学习记忆等生理功能密切相关,多表现 为增强学习记忆 [26][27][28][29][30] ;另一方面,成体海马神经发生在多种神经系统疾病中表现出新生水平异 常,如重度抑郁、焦虑、神经退行性疾病和癫痫 [17,[31][32][33][34][35][36] 等,提示成体海马神经发生可能参与这 些疾病的病理机制。近年来,随着研究手段的发展,研究表明调节成体海马神经发生水平不仅 可以对癫痫产生影响,还可以改善癫痫伴随的症状,提示成体海马神经发生可能作为新的干预 靶点,参与癫痫及其共患病的发展 [37][38][39][40] [18,43,44] 。在 Pilo 诱导 SE 的大鼠模型中,Parent 等使用了胸腺嘧啶核苷类似物(BrdU, [43] 。同样地,大鼠杏仁核电点燃的 结果表示, 大鼠在经过 9 次及以上的电点燃大发作后, 其细胞增殖水平增加了 2-3 倍 [44] 。 此外, 临床颞叶癫痫患者的海马标记染色也证实了成体新生神经元的增加 [45] 。 与初始 SE 阶段不同的是, 后续慢性期不同阶段的成体神经新生水平截然相反。 研究发现, 在急性癫痫发作期,成体神经新生水平表现为一过性的增加,在癫痫发作后期成体神经发生逐 渐降低至基础值,甚至在损伤后一个月左右低于基础水平 [18,46,47] 。Hattiangady 等人使用双皮 (KA 注射 5 个月后)成体新生神经元数量与同龄对照组相比降低了 64% [46] 。同样,Heinrich 等人也发现小鼠在经历过初始癫痫发作后,成体神经新生水平会在 KA 注射 7 天后逐渐下降并 且在 4 周后低于基础水平,在 6 周后的成体海马神经发生水平甚至降低到基础水平的 20%左右 [47] 。此外,研究者们在观察 SE 后新生乳鼠的神经新生水平时,得到了与成年动物完全相反的 结果。与成年动物在致痫性损伤后神经发生水平呈现一过性增加相反的是,在 SE 后的急性期 新生乳鼠的新生神经水平表现出明显下降, 而在 SE 后 2 个月的慢性期表现出轻微的增加 [48,49]…”
unclassified